2018
DOI: 10.1007/s12104-018-9818-3
|View full text |Cite
|
Sign up to set email alerts
|

1H, 13C and 15N backbone NMR chemical shift assignments of the C-terminal P4 domain of Ahnak

Abstract: Ahnak is a ~ 700 kDa polypeptide that was originally identified as a tumour-related nuclear phosphoprotein, but later recognized to play a variety of diverse physiological roles related to cell architecture and migration. A critical function of Ahnak is modulation of Ca signaling in cardiomyocytes by interacting with the β subunit of the L-type Ca channel (Ca1.2). Previous studies have identified the C-terminal region of Ahnak, designated as P3 and P4 domains, as a key mediator of its functional activity. We r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…AHNAK can be involved in a wide range of biological processes ( Figure 1 ). It has been recently reported that AHNAK plays a critical role in the regulation of calcium channels, blood-brain barrier formation, embryonic development, lipid metabolism, membrane repair, inflammatory responses and other processes ( 11 ). However, compared to AHNAK, the function of AHNAK2 is still relatively poorly studied and its biological function is not well defined.…”
Section: Functional Introduction To the Ahnak Familymentioning
confidence: 99%
“…AHNAK can be involved in a wide range of biological processes ( Figure 1 ). It has been recently reported that AHNAK plays a critical role in the regulation of calcium channels, blood-brain barrier formation, embryonic development, lipid metabolism, membrane repair, inflammatory responses and other processes ( 11 ). However, compared to AHNAK, the function of AHNAK2 is still relatively poorly studied and its biological function is not well defined.…”
Section: Functional Introduction To the Ahnak Familymentioning
confidence: 99%